2017
DOI: 10.1111/pce.12904
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the UVR8 photoreceptor in different tissues reveals tissue‐autonomous features of UV‐B signalling

Abstract: The Arabidopsis UV-B photoreceptor UV RESISTANCE LOCUS 8 (UVR8) orchestrates the expression of hundreds of genes, many of which can be associated with UV-B tolerance. UV-B does not efficiently penetrate into tissues, yet UV-B regulates complex growth and developmental responses. To unravel to what extent and how UVR8 located in different tissues contributes to UV-B-induced responses, we expressed UVR8 fused to the YELLOW FLUORESCENT PROTEIN (YFP) under the control of tissue-specific promoters in a uvr8 null mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 56 publications
5
28
0
1
Order By: Relevance
“…To verify the possibility that DES1 was physiologically associated with H 2 S production, the production of endogenous H 2 S levels in guard cells was examined using a H 2 S fluorescent probe (7-Azido-4-methylcoumarin). As expected, compared with the wild-type, the basal or ABA-induced 7-Azido-4-methylcoumarinassociated fluorescence levels were significantly lower in guard cells of two des1 mutant alleles, respectively (Figure 2a respectively (Bauer et al, 2013;Bernula et al, 2017;Cominelli et al, 2011;Mitra, Choi, & An, 1989). At least three independent transgenic lines were created in this study, and the existence of GFP fusion protein was validated by confocal laser scanning microscopy (CLSM).…”
Section: Aba Induces Guard Cell In Situ Des1 Expression and H 2 S Psupporting
confidence: 67%
See 1 more Smart Citation
“…To verify the possibility that DES1 was physiologically associated with H 2 S production, the production of endogenous H 2 S levels in guard cells was examined using a H 2 S fluorescent probe (7-Azido-4-methylcoumarin). As expected, compared with the wild-type, the basal or ABA-induced 7-Azido-4-methylcoumarinassociated fluorescence levels were significantly lower in guard cells of two des1 mutant alleles, respectively (Figure 2a respectively (Bauer et al, 2013;Bernula et al, 2017;Cominelli et al, 2011;Mitra, Choi, & An, 1989). At least three independent transgenic lines were created in this study, and the existence of GFP fusion protein was validated by confocal laser scanning microscopy (CLSM).…”
Section: Aba Induces Guard Cell In Situ Des1 Expression and H 2 S Psupporting
confidence: 67%
“…It was reported that DES1 is expressed in the cytosol of both epidermal and mesophyll cells, including the guard cells (Laureano‐Marín et al, ). To elucidate the tissue‐related DES1 function, we expressed DES1‐GFP protein in the des1 mutant background under the control of pML1 , pCAB3 , and pMYB60 promoters that have already been used in multiple studies to express proteins of interest in epidermal cells (including guard cells), mesophyll cells and guard cells, respectively (Bauer et al, ; Bernula et al, ; Cominelli et al, ; Mitra, Choi, & An, ). At least three independent transgenic lines were created in this study, and the existence of GFP fusion protein was validated by confocal laser scanning microscopy (CLSM).…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with its importance in regulating protective gene expression, with less UVR8 expression in mesophyll cells, and none detected in vascular tissue. 90 Epidermal UVR8 was shown to be involved in mediating the suppression of cotyledon expansion and hypocotyl growth by UV-B, as well as flavonoid biosynthesis. In mesophyll cells, UVR8 also regulated flavonoid biosynthesis and hypocotyl growth.…”
Section: (D) Stress-induction and Information Acquisition Are Intertwmentioning
confidence: 99%
“…Alternatively, after 3 days, plates were placed under continuous white light (PHILIPS TL-D 18 W/33-640 tubes, 10 μ mol m −2 s −1 ) supplemented with UV -B (PHILIPS ULTRAVIOLET-B TL20W/01RS tubes, 1.5 μ mol m −2 s −1 )) for 4 days at 22 °C. The seedlings were covered with transmission cut-off filters (WG series, Schott), using the WG305 filter for UV-B-treated seedlings (+UV-B), and the WG385 filter for the control (-UV-B) seedlings as providing half maximal transmission at 305 or 385 nmm, respectively (Bernula et al, 2017). Brachypodium distachion (Bd21) seeds were sown on 1% agar and kept at 4 o C for 5 days and were treated with 24 h white light (130 μmol m −2 s −1 ) to induce even germination.…”
Section: Plant Growth Conditions and Light Treatmentsmentioning
confidence: 99%